Sustained organic loading disturbance favors nitrite accumulation in bioreactors with variable resistance, recovery and resilience of nitrification and nitrifiers - E. Santillan (Nature Portfolio, 2020)
Abstract Sustained disturbances are relevant for environmental biotechnology as they can lead to alternative stable states in a system that may not be reversible. Here, we tested the effect of a sustained organic loading alteration (food-to-biomass ratio, F:M, and carbon-to-nitrogen ratio, C:N) on activated sludge bioreactors, focusing on the stability of nitrification and nitrifiers. Two sets of replicate 5-L sequencing batch reactors were operated at different, low and high, F:M (0.19–0.36 mg COD/mg TSS/d) and C:N (3.5–6.3 mg COD/mg TKN) conditions for a period of 74 days, following 53 days of sludge acclimation. Recovery and resilience were tested during the last 14 days by operating all reactors at low F:M and C:N (henceforth termed F:M–C:N). Stable nitrite accumulation (77%) was achieved through high F:M–C:N loading with a concurrent reduction in the abundance of Nitrospira. Subsequently, only two of the three reactors experiencing a switch back from high to low F:M–C:N recovered the nitrite oxidation function, with an increase in Nitrobacter as the predominant NOB, without a recovery of Nitrospira. The AOB community was more diverse, resistant and resilient than the NOB community. We showed that functional recovery and resilience can vary across replicate reactors, and that nitrification recovery need not coincide with a return to the initial nitrifying community structure.